The Molecular Structure of Fibrinogen - Murano, Genesio (Seminars in Thrombosis and Hemostasis, 2023)
Seminars in Thrombosis and Hemostasis (STH) celebrates 50 years of publishing in 2024. To celebrate this landmark event, STH is republishing some archival material. This manuscript represents the first full paper ever published in STH. The manuscript published without an abstract, and essentially covered in considerable detail the molecular structure of fibrinogen, as was known at that time. Fittingly, it covers some historical perspectives, the physicochemical properties and structure of fibrinogen across several species of animals (including humans) and its transformation into fibrin. We hope the readers of STH enjoy this journey into the past. This manuscript is accompanied by a Commentary that reflects on this past, as well as the journey towards contemporary understanding of the molecular structure of fibrinogen. As this is a republication of archival material, transformed into a modern format, we apologise in advance for any errors introduced during this transformation.
Keywords: fibrinogen; history; molecular structure; physicochemical properties; fibrin